Effect on mechanical and physical properties of paper by variating ratios of OCC Pulps and Virgin Sesbania grandiflora Pulps - Ravindra, Mohana (2019)
Pulp and paper industries known as most environmental polluting industries in past few decades. The high demand for paper production commits serious impact to environment and also lead to natural resource exploitation. Usage of recycled fibers in paper production is one of the alternative option to overcome these environmental issues. Even though, recycled fibers tend to give unsatisfied impact on strength properties of paper, addition of virgin pulp can lead to progression in strength properties of the paper. Sesbania grandiflora, known as fast growing short lived tree which are abundant in Malaysia. In this study, OCC pulp was added to virgin Sesbania grandiflora pulp in different ratios such as 25%, 50%, 75% and 100%. The physical properties such as thickness, brightness and opacity followed by mechanical properties such as burst strength, tearing strength and folding endurance was analyzed in this study accordance with TAPPI standard. The physical properties analysis showed that the thickness and brightness decreases with the addition of OCC pulp but the hand sheets has high opacity. For the mechanical properties analysis, the burst strength, tearing strength and folding endurance showed an increasing trend. Based on the overall results, the addition of OCC pulp to virgin Sesbania grandiflora pulp able to give a positive impact to the mechanical and physical properties of the paper.